EPEN-13. NOVEL LSD-1 INHIBITOR VALIDATION IN NEWLY ESTABLISHED PFA EPENDYMOMA PATIENT-DERIVED ORTHOTOPIC XENOGRAFT (PDOX) MODELS. Issue 2 (22nd June 2018) - Zhao, Sibo; Zhang, Huiyuan; Qi, Lin; Lindsay, Holly; Du, Yuchen; Braun, Frank; Kogiso, Mari; Injac, Sarah; Song, Yongcheng; Li, Xiao-Nan
Abstract: BACKGROUND: Posterior fossa A (PFA) ependymoma (EPN) has one of the worst prognosis in children and is primarily driven by epigenetic changes. In this study, we established a series of PFA EPN PDOX models from fresh surgical patient specimens. We also examined the therapeutic efficacy of SYC-836, a novel LSD-1 inhibitor compound, in these models. METHODS: EPN patient samples obtained from Texas Children's Hospital were directly implanted into NOD/SCID mouse brains. Tumorigenic xenograft tumors were serially subtransplanted for 5 generations. Detailed morphologic, histologic, and molecular comparisons were completed between xenograft and patient tumors. To examine in vitro activities, primary cultured cells from a PFA EPN cell line were subjected to SYC-836 at various concentrations (0-25uM). Cell viability and proliferation were measured over 14 days. To validate the drug's in vivo efficacy, 2 PDOX models were utilized. 40 SCID mice/model were implanted with tumor cells and divided into 4 treatment groups each: 1) control, 2) radiation, 3) SYC-836 only, and 4) combination (radiation + SYC-836). Animal survival times were analyzed using log rank analysis. RESULTS: We successfully developed 6 posterior fossa EPN xenografts models. It can be cryopreserved for long-term maintenance of tumorigenicity. Xenograft tumors precisely replicated characteristics of the patient tumors. SYC-836 demonstrated effective cell killing in vitro . IC50 was ~7.5uM. There were no survival benefit with either XRT or SYC-836 only when compared to the control group; however, when used in combination, the treatment strategy lead to significant improvement in animal survival. SYC-836 was well tolerated in mice.